(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3Gdbhd ai JChjd bhd Gddg Ld KfGDg (B" (3Gddg dG Edg EdG gh GdMi Gdbjhe (B" (3bOO ddfGai eG eVi Ydi JChjd bhd Gddg Ld KfGDg s
(3BNQgG (B:s
(3MOKfG SYjO Yf CHj ESMb Cf eYGPG cGf GPG aQZ ef gPg GdShQI hGfUQfG Ydi Gdbhe GdcGaQjf (B" (3bd Cejf BNQ JaSjQ ShQI GdHbQI Je GdSaQ GdKGef s
(3CKfGA JaSjQ ShQI GdHbQI hHEfJgGFg JeGe GdShQIcJHJ gPg GdfSNI Ydi Qb ZRGds
(3GdfSNI ef JMHjS GdSdWGf CHh YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(37 / 80) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs